Dangerous kiss : a novel - Collins, Jackie (New York, NY : Simon & Schuster, 1999)
The gun-totting Hollywood film director, Lucky Santangelo, daughter of a Mafia gangster, shoots a psychopath threatening her third husband, Lennie. At the same time she agrees to raise Lennie's illegitimate son, the fruit of a one-night stand in Sicily. By the author of Vendetta
The brassy, beautiful heroine of Lucky and Chances, Lucky Santangelo, returns to avenge the death of two close friends in a carjacking, a mission that entangles her with the U.S. president and leads to scandal. 300,000 first printing.
Keywords: Santangelo, Lucky (Fictitious character) -- Fiction; Motion picture industry -- California -- Los Angeles -- Fiction; Businesswomen -- Fiction; Los Angeles (Calif.) -- Fiction; Romantic suspense novels